Demyelinating diseases of the central nervous system registry for patients with traditional Chinese medicine: Rationale and design of a prospective, multicenter, observational study - Liu, Jia; Zhang, Chi; Xie, Yao; Zhou, Li; Guo, Li; Li, Bin; Jia, Zhen; Zhang, Jingze; Sugimoto, Kazuo; Gao, Ying (Frontiers in Pharmacology, 2022)
Background: Traditional Chinese medicine (TCM), a main form of complementary and alternative medicine provides a potential possibility for demyelinating disease of the central nervous system (DDC) management and has been applied in considerable amounts of patients with this disorder. Nevertheless, powerful real-world evidences regarding the epidemiological and clinical characteristics, safety, and outcomes of TCM in DDC are lacking. The primary objective of the Demyelinating Diseases of the Central Nervous System Registry for Patients with Traditional Chinese Medicine (DATE-TCM) is to create an organized multicenter data collection structure to define integrative characteristics of DDC patients treated with TCM in an endeavor to fill these knowledge gaps to better inform clinical care and health policy. Method: This study provides a prospective and voluntary registry by using a web-based system. Baseline data will be recorded and subsequently regular follow-up visits will be implemented every 3-6 months for a total of 5 years. The primary outcome is Annualized Aggregate Relapse Rate at 5-years follow-up. Results: DATE-TCM is currently designed to capture the multidimensional (epidemiologic, demographic, clinical, etc.) features of DDC patients receiving TCM treatment, the type and long-term safety and efficacy of TCM intervenes in the DDC populations, as well as the interaction of TCM treatments and disease modifying therapies in the management of DDC, aiming to include 2000 eligible adult DDC patients with TCM intervenes from 35 participating centers, covering 77.4% of provincial administrative regions of mainland China. Conclusion: DATE-TCM is the first, largest, most geographically extensive, and standard registry-based observational study that systematically document the real-world data regarding the TCM application in the DDC populations, which will be extraordinarily important for clarifying the comprehensive characteristics and outcomes of TCM in DDC, further shed light on standardizing and optimizing the TCM measures for DDC management and establishing evidence-based clinical practice guidelines for TCM application in DDC.